Система науки про аудит - Кужельний, М. В.; Давидов, Г. М. (КНТУ, 2005)
Визначений процес пізнання в аудиті, який досяг теоретичного рівня наукової стадії мислення. Розроблена система науки про аудит, яка відображає передумови виникнення науки, її функції і риси. Центральне місце в конструкції науки про аудит займають її форма і системи, за допомогою яких реалізується загальна логіка науки про аудит. Визначена в розрізі окремих функцій, систем, аспектів і елементів структура наукового знання в аудиті. Розроблена власна логічна система науки про аудит, центральним місцем якої є чітке виділення предмету і методу науки про аудит, що є визначальним у перетворенні знання про аудит в науку. The process of cognition in an audit which attained the theoretical level of scientific stage of thought has been developed. The system of science about an audit which represents pre-conditions of origin, functions and science line have been developed. The forms and systems which give an opportunity to realize general logic of science about an audit are engaged the central seat in construction of science about an audit. The structure of scientific knowledge in an audit is defined in the cut of separate functions, aspects and elements. The own logical system of science about an audit have been developed. The strict selection of object and science method about an audit are engaged the central moment of this system in a great deal determining in transformation of knowledge about an audit in science.
Keywords: аудит; пізнання; система; наука; структура; логіка